2015
DOI: 10.1371/journal.pone.0122901
|View full text |Cite
|
Sign up to set email alerts
|

Three Novel Herpesviruses of Endangered Clemmys and Glyptemys Turtles

Abstract: The rich diversity of the world’s reptiles is at risk due to significant population declines of broad taxonomic and geographic scope. Significant factors attributed to these declines include habitat loss, pollution, unsustainable collection and infectious disease. To investigate the presence and significance of a potential pathogen on populations of critically endangered bog turtles (Glyptemys muhlenbergii) as well sympatric endangered wood (G. insculpta) and endangered spotted (Clemmys guttata) turtles in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 30 publications
1
36
0
1
Order By: Relevance
“…All currently recognized reptilian herpesviruses belong to the subfamily Alphaherpesvirinae and chelonian herpesviruses are the best characterized of these (Wellehan and Johnson 2005;Ariel 2011;Marschang 2011;Wellehan 2012). Chelonian herpesviruses form a monophyletic cluster consistent with a genus, which has been called Chelonivirus Ossiboff et al 2015b), Glyptemys herpesvirus 1 and 2 (Ossiboff et al 2015b), and Terrapene herpesvirus 1 and 2 (Sim et al 2015;Yonkers et al 2015). Given the degree of relatedness and clinical similarities between Testudinid and Emydid herpesviruses and their hosts, the majority of discussion in this thesis will focus on these viruses.…”
Section: Overview Of Herpesviruses In Cheloniansmentioning
confidence: 99%
See 4 more Smart Citations
“…All currently recognized reptilian herpesviruses belong to the subfamily Alphaherpesvirinae and chelonian herpesviruses are the best characterized of these (Wellehan and Johnson 2005;Ariel 2011;Marschang 2011;Wellehan 2012). Chelonian herpesviruses form a monophyletic cluster consistent with a genus, which has been called Chelonivirus Ossiboff et al 2015b), Glyptemys herpesvirus 1 and 2 (Ossiboff et al 2015b), and Terrapene herpesvirus 1 and 2 (Sim et al 2015;Yonkers et al 2015). Given the degree of relatedness and clinical similarities between Testudinid and Emydid herpesviruses and their hosts, the majority of discussion in this thesis will focus on these viruses.…”
Section: Overview Of Herpesviruses In Cheloniansmentioning
confidence: 99%
“…Skin lesions represent a different clinical presentation in Emydids, including hyperkeratosis in an Australian Krefft's river turtle (Emydura macquarii krefftii) infected with an uncharacterized herpesvirus (Cowan et al 2015) and fibropapilloma in an Eastern box turtle infected with Terrapene herpesvirus 2 (Yonkers et al 2015). Mortalities without premonitory clinical signs (Jungwirth et al 2014) and infection in apparently healthy individuals (Ossiboff et al 2015a(Ossiboff et al , 2015bKane et al 2017) have been reported in Emydids. Interestingly, painted turtles (Chrysemys picta) have been implicated as possible asymptomatic carriers or a reservoir for Emydid herpesvirus 1 after being found in four apparently healthy individuals housed in the same system as a Northern map turtle (Graptemys geographica) that died with herpesvirus inclusions in the liver, lung, and spleen (Ossiboff et al 2015a).…”
Section: Herpesviruses In Freshwater and Box Turtles (Emydidae)mentioning
confidence: 99%
See 3 more Smart Citations